Physico Chemical Analysis of the Formulation Kanakabindhvarishtam (International Journal of Ayurveda and Pharma Research, 2022)
Kanakabindhvarishtam is a formulation included in Arishta kalpana. It is mentioned by Acharya Charaka in the context of Kushta chikitsa. The formulation is having Khadira (Acacia Catechu) as Kashaya Dravya (decoction) and Triphala (Amalaki, Vibeetaki, Hareetaki), Trikadu (Maricham, Sundi, Pippali), Vidanga, Mustha, Indrayava, Guduchi, Haridra, Daruharidra and Vasa Moola as Prakshepa Dravyas. Even though Guda and honey were not mentioned in the yoga, they were added in order to facilitate the fermentation process. Dhataki flowers which are commonly used to accelerate the fermentation process were not added in the preparation. The whole process were carried out in two stages- initial stage include the preparation of Kanakabindhvarishta according to the reference by Charaka Acharya, and in the 2nd stage Physico chemical analysis of the yoga were carried out. The Physico chemical parameters include pH value (5.28), total solid content (2.03%), specific gravity (1.0105), reducing sugar (2.8129%), total sugar (6.43%) and alcoholic content (8%). 35lt of Arishta was prepared by fermentation process. The Sandhana patra (fermentation vessel) in which the Arishta was prepared were kept for a period of 45 days and all the Arishta siddha lakshanas were obtained as per the reference